Effectiveness of Small Side Games 3v3 And 4v3 Training On Passing Accuracy In The Men's Futsal Team, Jakarta State University - Ramadhan, Muhammad Ilham; Nurfitranto, Nurfitranto; Apriyanto, Tirto (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2023)
The purpose of this study was to find out 1) The effectiveness of 3v3 small side game exercises compared to 4v3 exercises in increasing passing accuracy. 2) Knowing the effectiveness of the Small Side Games 3v3 and Small Side Games 4v3 exercises on the passing accuracy of the Jakarta State University Futsal team. Research data collection was carried out from March 8 2023 which took place at the Futsal Field Hall B, Jakarta State University. The research method used is a quantitative research method with quasi-experimental studies. This research is experimental, namely to determine the effect between variables. The population of this study was the Jakarta State University futsal team players, totalling 80 people, and the sample was 30 people using a purposive sampling technique. The results of the data analysis show that 1) Is the Small side games 3v3 exercise effective in increasing the passing accuracy of the Men's Futsal Team at Jakarta State University? 2) Is the 4v3 Small Side Games exercise effective in increasing the passing accuracy of the Jakarta State University Men's Futsal team, 3) Which is more effective, the 3v3 Small Side Games or 4v3 Small Side Games Exercise in increasing the Passing of the Jakarta State University Men's Futsal team.